Whitney Biennial 2006 : Day for night. - Andrews, Max; Burlap, Toni; Burton, Johanna; Carrion-Murayari, Gary; Eros, Bradley; Gangitano, Lia; Hainley, Bruce; Hudson, Suzanne; Huldisch, Henriette; Iles, Chrissie; Lee, Nathan; Lévy, Bernard-Henri; et al. (New York : Whitney Museum of American Art New York, 2006)
Allora & Calzadilla ; Anderson, Dawolu Jabari ; Anger, Kenneth ; Angerame, Dominic ; Battle, Christina ; Benning, James ; Berger, Laurent P. ; Blakemore, Amy ; Bourque, Louise ; Bradford, Mark ; Brauntuch, Troy ; Burdin, Anthony ; Bureau of Inverse Technology ; Butler, George ; Carter ; Caycedo, Carolina ; Center for Land Use Interpretation ; Chan, Paul ; Cheatle, Lori ; Cohen, Ira ; Colen, Dan ; Collier, Anne ; Conrad, Tony ; Corporation, Bernadette ; Critical Art Ensemble ; Cyrus, Jamal ; Davis, Miles ; Deep Dish Television Network ; DeGiulio, Lucas ; Doig, Peter ; Donnelly, Trisha ; Durham, Jimmie ; Evans, Kenya ; Fischer, Urs ; Gatten, David ; Gibbons, Joe ; Gober, Robert ; Graf, Deva ; Graham, Dan ; Graham, Rodney ; Greely, Hannah ; Grotjahn, Mark ; Heikes, Jay ; Henry, Doug ; Huyghe, Pierre ; Iannone, Dorothy ; Jackson, Matthew Day ; Jamie, Cameron ; Japanther ; Jeremijenko, Natalie ; Johnston, Daniel ; Klahr, Lewis ; Koether, Jutta ; Lampert, Andrew ; Lapinski, Lisa ; Larner, Liz ; Liden, Hanna ; Liotta, Jeanne ; Losier, Marie ; Maier-Aichen, Florian ; Majoli, Monica ; Masnyj, Yuri ; Mason, T. Kelly ; McEwen, Adam ; Mead, Taylor ; Meckseper, Josephine ; Minter, Marilyn ; Momus ; Monahan, Matthew ; Munro, JP ; Negron, Jesus "Bubu" ; Newkirk, Kori ; Norsten, Todd ; O'Rourke, Jim ; Otabenga Jones & Associates ; Oursler, Tony ; Parrino, Steven ; Paschke, Ed ; Poledna, Mathias ; Pruitt, Robert A. ; Reeves, Jennifer ; Serra, Richard ; Sibony, Gedi ; Smith, Jennie ; Snow, Dash ; Snow, Michael ; Spaulings, Reena ; Stingel, Rudolf ; Strassheim, Angela ; Strauss, Zoe ; Studio Film Club ; Sturtevant, Elaine ; Sullivan, Billy ; Suvero, Mark di ; Sweeney, Spencer ; Thater, Diana ; Tiravanija, Rirkrit ; Trecartin, Ryan ; Vasell, Chris ; Vezzoli, Francesco ; etc.
Whitney Biennial 2006 : Day for night, Whitney Museum of American Art New York, 2006-03-02. 2006-05-28
boek